Cutaneous Comorbidities Associated With Atopic Dermatitis in Israel: A Retrospective Real-World Data Analysis. (11th November 2022) - Leshem, Yael A.; Sugerman, Philip B.; Weil, Clara; Chodick, Gabriel; Liang, Huifang; Wang, Hongwei; Calimlim, Brian; Dorfman, Ana; Shalev, Varda; Amitai, Dan Ben
Abstract : Background: Patients with atopic dermatitis (AD) are susceptible to infectious and inflammatory cutaneous comorbidities. Objective: The aim of the study was to describe the prevalence of cutaneous comorbidities associated with AD, including their relationship with AD severity. Methods: A retrospective cross-sectional analysis was performed using the Israeli Maccabi Healthcare Services database. Prevalent AD cases on December 31, 2017, were diagnosed with AD at any time since 1998 and had 1 or more recent (2013–2017) AD diagnoses. Dispensed AD treatments within 5 or fewer years served as a surrogate for AD severity. Cutaneous comorbidities in AD cases were compared with non-AD controls matched 1:1 on age, sex, and residential area. Among adults, comorbidities were compared across AD severity using multinomial logistic regression. Results: The eligible population included 94, 483 patients with mild (57.7%), moderate (36.2%), or severe (6.1%) AD, and 94, 483 matched non-AD controls. Skin infections, inflammatory skin conditions, cutaneous manifestations of AD, and sweat gland disorders were more prevalent ( P < 0.001) in patients with AD than in controls. Most cutaneous comorbidities that were more prevalent in adult patients with AD were also significantly ( P < 0.001) associated with AD severity. Conclusions: This study suggests that AD is associated with many infectious and inflammatory cutaneous comorbidities and highlights the relationship between AD severity and comorbidity prevalence.